Effect of advanced milling on carbothermal reduction of pyrolusite (MnO2) by carbonized tea plant waste - Boyrazli, Mustafa; Ozturk, Elif Aranci (Elsevier, 2019)
This study examined the effect of advanced milling on carbothermal reduction of oxidized manganese ore using carbonized tea plant waste as reductant. For the carbothermal reduction of manganese oxide, the ratios of Mn/Fe, C/(MnO2+Fe3O4) and ball/mixture were 8/1, 2/1 and 10/1, respectively. Samples were subjected to advanced milling in an attritor mill for 10, 15, 20, 30, 60, 90 and 120 h. The rotation speed of the mill shaft was 350 rpm during the processes performed in the attritor. DTA-TG, SEM and XRD analyses were carried out to characterize the samples. When XRD peaks were compared for different grinding times, it was seen that all of the diffraction peaks gradually decreased in parallel with the increase in grinding time. The DTA-TG analysis of the samples subjected to mechanical activation for 120 h shows a symmetrical change, which is similar to the Gaussian function. The activated samples obtained from advanced milling were treated at 1000,1100,1200 and 1300 degrees C for 30, 60, 90 and 120 min in an argon atmosphere. The results of the experimental studies indicate that a 58.76% reduction occurred in the 120 h advanced milled samples subjected to treatment at 1300 degrees C for 2 h. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Advanced milling; Tea plant waste; Carbonization; Carbothermal reduction